Sistema de Informação Pré-Natal: análise crítica de registros em um município paulista. - Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Zina, Lívia Guimarães; Yarid, Sérgio Donha; Francisco, Kléryson Martins Soares (My University, 2010)
The prenatal assistance is one of the health care pillars. This study aimed to conduct a critical evaluation of the SIS Prenatal in a city of São Paulo State, to compare its data with the local assistance and to verify the registry of pregnant women attended at Health Care Centers. It was analyzed the pregnant women records through consultation at Health Regional Unit and municipal health service. There were inconsistencies between the system and local registry. The failures were related to the inadequate filling of attendance files, besides scarce control of pregnant women files and scheduling on health centers. The results suggest the need for better planning of actions for the improvement of prenatal service quality.
Prenatal Information System: critical analysis of register in a municipality of São Paulo State
Keywords: Brazil; cross-sectional study; female; human; information system; pregnancy; prenatal care; register; standard; statistics; Cross-Sectional Studies; Female; Humans; Information Systems; Pregnancy; Prenatal Care; Registries